Cleft lip and palate review: Epidemiology, risk factors, quality of life, and importance of classifications (Faculty of Medicine Universitas Indonesia, 2008)
Cleft lip with or without cleft palate is the most occurring craniofacial anomaly in human, resulting from a complex etiology involving multiple genetic and environmental factors. The defect carries lifelong morbidity and economic burden. Children with clefts will require continuous medical interventions for at least the first 18 years of life, affecting many aspects of their lives. The extent and complexity of clefts vary infinitely, later determining individual management and outcome. Identification and classification play significant roles in initial assessment of these unique cleft cases, which affect options for following correctional attempts. Some classifications even allow measurement of progress after anatomical repositioning, and success rate after surgical repairs. The challenge of developing one such widely inclusive classification is discussed. (Med J Indones 2008; 17: 226-39)